Термин «πάκτον» Константина Багрянородного в свете административных отношений в феме Херсон в середине Х века - Никифоров, М.А. (Материалы по археологии, истории и этнографии Таврии, 2008)
Трактат «Об управлении империей», авторство которого принадлежит византийскому императору Константину VII Багрянородному (945-959 гг.), является одним из важнейших письменных памятников по истории Византии. Сочинение, составленное между 948 и 952 годами, предназначалось для сына Константина, Романа и должно было служить ему руководством по управлению империей. Труд содержит обширные сведения по истории как самой Византии, так и различных политических образований, находящихся вблизи ее границ. Немалое внимание в трактате уделяется и Крымскому полуострову. According to chapter 53 of treatise by Constantine Porphyrogenitus «On Government of the Empire» strategus of Cherson cancelled 10 litrai paid to the fortress of Cherson from the treasury and 2 pounds of pakton in case of rebellion of its residents. Greek term pakton in the fieid of constitutional law was used in two main meanings; agreement, pact, and certain payment which in historiography are usually named as tribute. In the fragment from the treatise examined in this article the term pakton means tribute paid as a sign of subordination and dependence from the Emperor of Byzantium. As 2 litrai were paid to the fortress of Cherson, they were coliected from other territories dependent to Byzantium in Crimea, the so called clemates. Thus, political dependence of clemates from Byzantium in the mid-10“' century was, mainiy, in the form of paying yearly tribute - pakton. Besides paying pakton, local elite that had real power in clemates could take allied liabilities upon themselves.